Performance Analysis and Optimization of an Ammonia Stripper through Scrubber Integration Using Industrial Data and Aspen Hysys Simulation - Prahady Susmanto; Irsyadi yani; David Bahrin; Asty Maharani; Suci Anggraini (Candela Edutech Indonesia, 2026)
The stripping gas from the ammonia stripper still shows fluctuating ammonia (NH₃) content and, under certain conditions, has the potential to exceed the targeted limit. This study discusses the evaluation of the ammonia stripper output gas and efforts to reduce NH₃ levels by adding a scrubber unit as a further treatment using Aspen HYSYS V.11 simulation. However, previous studies have primarily focused on ammonia removal within the stripper unit under steady-state conditions, with limited investigation into the integration of scrubber systems to handle fluctuating industrial wastewater and steam flow conditions. Operational performance was evaluated using industrial data collected during August 6–10, 2025, by calculating NH₃ removal efficiency based on inlet–outlet concentrations, followed by Aspen HYSYS simulation using the Extended NRTL model to analyze the effect of wastewater flow rate and assess the optimization process through scrubber integration. The evaluation results show that before the addition of the scrubber, the NH₃ reduction efficiency in the ammonia stripper was in the range of 87.78–96.34% with an average value of 92.97%, but under conditions of high wastewater discharge, the NH₃ concentration in the stripping gas still increased. Scrubber integration simulations showed that the NH₃ concentration in the stripper exhaust gas decreased from 3.21% to 0.96%, equivalent to a reduction of approximately 70%, indicating significant emission optimization. These results indicate that the addition of a scrubber to the stripped gas is an effective alternative to control NH₃ emissions.